An extraordinary new termite (Isoptera: Termitidae: Syntermitinae: Rhynchotermes) from the pasturelands of northern Colombia - Scheffrahn, Rudolf H. (Zootaxa, 2010)
A new species of mandibulate nasute termite, Rhynchotermes bulbinasus Scheffrahn sp. nov. is described from dimorphic soldiers and monomorphic workers discovered in the Caribbean plains of northern Colombia. The new species differs from all other New World Syntermitinae and Nasutitermitinae, in having a nasus with its distal diameter greater than its median diameter. Literature on the genus Rhynchotermes Holmgren is reviewed and field observations of R. bulbinasus are given.